Kemampuan Pegawai dalam Mengimplementasikan Transformasi di Era Digitalisasi - Sajidatun Naflah; Basri Aramico; Mira Gusweni; Ramadhaniah (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
The advancement of information and communication technology has had a major impact on the health sector, including at the Banda Raya Health Center in Banda Aceh City. However, some employees still face technical obstacles and do not understand the digital system. This study aims to analyze employee capabilities in implementing digital transformation in 2025. The study is descriptive analytical with a cross-sectional approach, involving all employees (56 people) as samples. Data were collected through interviews and observations using questionnaires and checklists, then analyzed univariately and bivariately using STATA 17.0. The results showed that 48.21% of employees had low skills, 28.57% had a less supportive work culture, 42.86% had poor internal communication, 30.36% had poor knowledge, 35.71% did not receive training, 69.64% were middle-aged, and 100% had limited technological infrastructure. Bivariate analysis showed a significant relationship between work culture (p=0.002), internal communication (p=0.003), knowledge (p=0.027), and training (p=0.015) with employee capability, and there was no significant relationship between age variable and employee capability (p=0.0487). However, no relationship was found between age and employee capability, and infrastructure variables were not analyzed because they did not vary. It is recommended to improve training, counseling, infrastructure provision, and explore other factors such as motivation and leadership style.